The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/nu8100619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Almond- and Olive Oil-Based Docosahexaenoic- and Vitamin E-Enriched Beverage Dietary Supplementation on Inflammation Associated to Exercise and Age

Abstract: n-3-polyunsaturated fatty acids and polyphenols are potential key factors for the treatment and prevention of chronic inflammation associated to ageing and non-communicable diseases. The aim was to analyse effects of an almond and olive oil beverage enriched with α-tocopherol and docosahexaenoic, exercise and age on inflammatory plasma markers, and immune gene expression in peripheral blood mononuclear cells (PBMCs). Five young and five senior athletes who were supplemented for five weeks with a functional bev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 66 publications
4
25
0
Order By: Relevance
“…Epidemiological studies have shown a relationship between the Mediterranean diet and a lowered incidence of pathologies such as cancer, atherosclerosis, cardiovascular and neurodegenerative diseases . A key role in this diet's protective action is played by the presence of olive oil . Olive extracts are a natural source of polyphenols, widely considered to be potentially beneficial for health.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown a relationship between the Mediterranean diet and a lowered incidence of pathologies such as cancer, atherosclerosis, cardiovascular and neurodegenerative diseases . A key role in this diet's protective action is played by the presence of olive oil . Olive extracts are a natural source of polyphenols, widely considered to be potentially beneficial for health.…”
Section: Introductionmentioning
confidence: 99%
“…But horses having a higher frequency of interaction with their owners tend to receive more nutritional attention; a proposition that is supported by others who observe that people caring for fewer horses tend to have horses that are more overweight than people who are caring for a greater number of horses (Hitchens, Hultgren, Frössling, Emanuelson, & Keeling, ). Further support for the role of AL is evidence that high intensity exercise increases PL‐PGE 2 in equine (Lindinger, MacNicol, Karrow, & Pearson, ) and human athletes under acute exercise conditions (Capó, Martorell, Sureda, Riera et al., ; Capó, Martorell, Sureda, Tur, & Pons, ); an effect that may be augmented, at least in part, by increased production of PGE 2 by polymorphonuclear cells taken from trained vs untrained individuals (Capó, Martorell, Sureda, Riera et al., ). PGE 2 is an important contributor to adaptation to and/or recovery from exercise by inducing vasodilation (Capó, Martorell, Sureda, Riera et al., ), muscle hypertrophy (Burd et al., ) and resolution of inflammation (Serhan, ).…”
Section: Discussionmentioning
confidence: 98%
“…Further support for the role of AL is evidence that high intensity exercise increases PL‐PGE 2 in equine (Lindinger, MacNicol, Karrow, & Pearson, ) and human athletes under acute exercise conditions (Capó, Martorell, Sureda, Riera et al., ; Capó, Martorell, Sureda, Tur, & Pons, ); an effect that may be augmented, at least in part, by increased production of PGE 2 by polymorphonuclear cells taken from trained vs untrained individuals (Capó, Martorell, Sureda, Riera et al., ). PGE 2 is an important contributor to adaptation to and/or recovery from exercise by inducing vasodilation (Capó, Martorell, Sureda, Riera et al., ), muscle hypertrophy (Burd et al., ) and resolution of inflammation (Serhan, ). While the precise nature of the interaction between PGE 2 and exercise has not been defined, it is known that blockade of exercise‐induced PGE 2 production in athletes by administration of non‐steroidal anti‐inflammatory drugs increases oxidative stress associated with the exercise bout (McAnulty et al., ), and inhibits exercise‐induced muscle protein synthesis (Trappe, White, Lambert, Hellerstein, & Evans, ).…”
Section: Discussionmentioning
confidence: 98%
“…Muscle and erythrocyte FAs composition patterns change with the age. Age is a factor that alters the FAs composition of plasma and erythrocytes between young and senior athletes (22.3 ± 3.8 and 45.6 ± 1.6 years respectively) [9, 10]. Young children have more PUFAs than adults in muscle and erythrocytes [17].…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid (FA) composition of the diet is known to influence the FAs composition of stored and structural lipids in different body parts, such as serum/plasma lipids [5-10], erythrocyte membranes [7, 9-11], buccal epithelial cells [12], adipose tissue [13, 14], skeletal muscle [15-19] and immune cells [20]. Dietary FAs influence FAs incorporation into the cell membranes modulating their cellular functions [21-25].…”
Section: Introductionmentioning
confidence: 99%